Determination of refractive index dispersion and thickness of thin antireflection films TiO₂ and Si₃N₄ on surfaces of silicon photoelectric converters - Donets, V.V.; Melnichenko, L.Y.; Shaykevich, I.A.; Lomakina, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Offered in this work is the method to determine the thickness and refractive index dispersion of thin antireflection films on absorbing substrates by using a spectral dependence of reflectivity at normal light incidence. The method has been applied to determine the above characteristics of thin antireflection films TiO₂ and Si₃N₄ on surfaces of silicon photoelectric converters. The films were prepared by chemical sedimentation. The obtained experimental data have been treated using a computer program to deduce dispersion curves and thickness values. The results have been interpreted.